Growth in very preterm children: Head growth after discharge is the best independent predictor for cognitive outcome. (December 2016) - Lidzba, Karen; Rodemann, Susanne; Goelz, Rangmar; Krägeloh-Mann, Ingeborg; Bevot, Andrea
Abstract: Background: The contribution of growth parameters to the cognitive outcome of very low birth weight (VLBW)/very preterm (VP) infants is difficult to disentangle from other preterm-birth related factors. Aims: We hypothesized that long-term cognitive and motor outcome of VLBW/VP infants is most strongly associated with growth in head circumference after hospital discharge. Study design: Single-centre prospective longitudinal study: anthropometric measures at different time points (birth, discharge, school-age). Subjects: 136 VLBW/VP infants (< 32 weeks gestation/birth weight < 1.500 g). Outcome measures: Cognitive and motor function (Kaufman Assessment Battery for Children; Movement Assessment Battery for Children) at school-age (6.7–10.0 years, mean = 8.2). Results: In hierarchical multiple regression analyses, growth from birth to discharge significantly predicted cognitive outcome (weight: R 2 change = 0.063, p = 0.014; length: R 2 change = 0.078, p = 0.007; HC: R 2 change = 0.050, p = 0.030), as well as weight gain ( R 2 change = 0.096, p = 0.001) and head growth ( R 2 change = 0.134, p < 0.001) from discharge to school-age. While most growth parameters, especially those from birth to discharge, were significantly influenced by prenatal growth and immaturity related morbidity ( R 2 = 0.151 to 0.605, all p ≤ 0.001), head growth after discharge was not ( R 2 = 0.029, p = 0.461). Conclusions: Amongst all anthropometric measures, head growth between discharge and school-age is the best independent predictor for cognitive outcome in VLBW/VP infants. Determinants of head growth after discharge need further studies to identify targets for intervention. Highlights: Growth between birth and discharge predicts cognitive outcome of very preterm infants. In very preterm infants, early growth is strongly associated with immaturity and smallness at birth. Head growth after discharge is the best independent predictor for cognitive outcome of very preterm infants.